Perencanaan Kerja Sama dengan Lembaga Penyiaran dalam Mengkampanyekan Pesan Kerukunan pada Televisi - I Putu Putra Yasa (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describes the issue of maintaining harmony as a top priority, because harmony is the authorized capital in nation building. The Ministry of Religion in Tabanan District is obliged to campaign for harmony. Harmony campaign is through the display of public service advertisements on television. The policy in the form of automatic adjustment is an obstacle in achieving performance targets. The achievement must not stop. Instead, solutions must be found so that targets are still achieved. Cross-sectoral cooperation between the Ministry of Religion and broadcasting institutions is a necessity. Therefor planning is carried out that is intended to provide information as a basis for policy making of harmony campaigns. The goals are: (1) Planning the achievement of several performance targets in one cooperative activity by displaying the public service advertisements on television; (2) Streamlining cost expenditures through the display of public service advertisements on television with a cooperation scheme between the government and business entities; (3) Streamlining the delivery of a harmony message with the target of people who actively access television. The method used is descriptive with a qualitative approach. Data are collected from various literature sources and analyzed the external factors to see the challenges and potentials that exist. Based on the analysis, the recommended policy choice is cooperation between the Ministry of Religion in Tabanan Disctrict and the Public Broadcasting Institution to convey harmony through public service advertisements on television. Keywords: planning, cooperation, harmony, television